PENGELOLAAN SAMPAH DI MI NURUL QUR'AN PAGUTAN: UPAYA MENINGKATKAN PEMAHAMAN EKOLOGI SISWA MELALUI PRAKTIK LINGKUNGAN - Purnawirawan, Purnawirawan; Wardi, Muhammad Musfiatul; Aqodiah, Aqodiah (Ibtida'iy : Jurnal Prodi PGMI, 2024)
This study aims to describe and analyze the waste management process at MI Nurul Qur'an Pagutan and its influence on improving students' ecological understanding. The type of research used is qualitative descriptive research with a phenomenological approach, which observes waste management practices in schools and their influence on students' environmental awareness. Data were collected through participatory observation, interviews with teachers and students, and documentation related to waste management policies and activities at the madrasah. The results of the study indicate that the waste management program at MI Nurul Qur'an has succeeded in forming positive habits among students, such as disposing of waste in its place and maintaining the cleanliness of the school environment. This program not only aims for cleanliness, but also to instill ecological values and environmental responsibility in students. However, there are obstacles that reduce the effectiveness of the program, such as the lack of student discipline in sorting waste and limited supporting facilities, such as trash bins and recycling facilities. In addition, students' ecological understanding still needs to be improved, especially in connecting theoretical knowledge with daily practice. This study suggests that schools should integrate more project-based practical activities in ecology learning to deepen students' understanding of environmental issues, as well as improve facilities and involve experts in waste management to support the sustainability of the program.